1997
DOI: 10.1097/00004424-199707000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging in the Diagnosis of Acute Injured Distal Tibiofibular Syndesmosis

Abstract: Magnetic resonance imaging of the syndesmotic complex is a highly sensitive and specific tool for the pretherapeutic-evaluation of syndesmotic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 11 publications
2
69
1
3
Order By: Relevance
“…After acute trauma, MRI has high sensitivity, specificity, and accuracy to determine the level of injury to the ankle syndesmotic ligaments. 20,21 Evidence Category: B…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…After acute trauma, MRI has high sensitivity, specificity, and accuracy to determine the level of injury to the ankle syndesmotic ligaments. 20,21 Evidence Category: B…”
Section: Diagnosismentioning
confidence: 99%
“…97,37 For evaluation of the ankle syndesmotic ligaments after acute injury, MRI has high sensitivity and specificity, with the former ranging from 93% to 100% and the latter ranging from 96% to 100%. 20,98 Disadvantages of MRI for acute ankle injuries include cost, lack of accessibility in the average clinical setting, and time required for the test. Diagnostic ultrasound has gained increased popularity as an alternative to MRI because it is portable and less expensive and provides immediate and dynamic images for interpretation.…”
mentioning
confidence: 99%
“…Scranton 43 has proposed that CT has less value for soft tissue injuries because only bony details can be identified. Vogl et al 55 and Oae et al 37 have demonstrated that distal tibiofibular syndesmosis injuries can be visualized with high sensitivity and specificity using MRI. MRI analysis of the syndesmotic injury also has a significant association with secondary findings, such as anterior talofibular ligamentous injury, osteochondral lesions, bone bruise (acute syndesmosis injury), and distal tibiofibular joint incongruity.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…there are no clinical studies using ct to evaluate the stability of the fractured ankle. Mri provides additional information about concomitant soft tissue, especially delta ligament and syndesmotic injuries (vogl et al 1997, nielson et al 2004, Gardner et al 2006c, beumer 2007, Koval et al 2007, cheung et al 2009), but it does not aid assessment of syndesmosis stability. ultrasound, when compared to Mri, has been reported to have a sensitivity of 0.66 and a specificity of 0.91 (Milz et al 1998); however, the validity of ultrasound imaging is dependent on the experience of the examiner, and ultrasound is not performed routinely for diagnosis of syndesmosis injuries (beumer 2007).…”
Section: Mechanism Of Injury and Classificationmentioning
confidence: 99%